APRESIASI KONSUMEN TERHADAP MEREK (BRAND) DALAM NEGERI - Hamdani Surachman; Guido Benny (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
Brand is one of the strategies in marketing but development of brand requires a long term investment, especially for advertising, promotion and packaging. Nowadays many manufacturers finally realized that market captured is precisely can be done by building a brand itself in the country, so that the brand can earn loyalty from customers. The significance of developing brands for businesses (SMEs) and Government is increasing competitiveness, value added, prosperity and the national economy situation. Indonesia, which is manufactures a variety of products, both agricultural and industrial exports more products using the foreign brands, so the value added enjoyed by holders of foreign brand. To establish and develop brands, need to do a few things such as create A Single Brand (model sakasame), socialize brand development (through seminars, exhibitions or the mass media), and formed an agency of Indonesia brand development.